Determination of Toddler Stunting in Indonesia 2020–2023 from an Economic Perspective - Rianita Maharani; Sitti Retno Faridatussalam (Universitas KH. Abdul Chalim Mojokerto, 2026)
Stunting is a condition characterized by stunted growth and development in children caused by nutritional problems, infectious diseases, and various other factors that can affect children's health. The purpose of this study was to analyze the factors influencing the prevalence of stunting in toddlers in 34 provinces in Indonesia during the period 2020-2023. The variables analyzed included Egg Protein Consumption (KPT), Access to Clean Water (AAB), Access to Health Services (ALK), Average Years of Schooling for Girls (RLSP), and Family Planning (KB). This study used panel data regression analysis with a cross-sectional sample of 34 provinces and a time series sample of 2020-2023. Data were obtained from the Indonesian Central Bureau of Statistics and the Ministry of Health. After conducting the Chow and Hausman tests, the best estimation model for this study was the Fixed Effect Model (FEM). The results of this study indicate that access to clean water and average years of schooling for girls have a significant negative effect on stunting. Meanwhile, egg protein consumption, access to health services, and family planning did not show a significant effect on stunting in the 34 provinces in Indonesia.